EMPOWERING THE STUDENTS’ ABILITY IN WRITING THROUGH THE IMPLEMENTATION OF PLEASE STRATEGY (A Collaborative Classroom Action Research for the Tenth Grade Student of SMAN 2 Kuta Makmur): EMPOWERING THE STUDENTS’ ABILITY IN WRITING THROUGH THE IMPLEMENTATION OF PLEASE STRATEGY (A Collaborative Classroom Action Research for the Tenth Grade Student of SMAN 2 Kuta Makmur) - Nora Russaifa; Eli Nofriati (Journal of English Education and Social Science, 2021)
This thesis entitled empowering the students’ ability in writing through the implementation of please strategy (A Collaborative Classroom Action Research to the tenth Grade Student of SMA Negeri 2 Kuta Makmur). The problems of this research are; 1) How can the implementation of PLEASE strategy empowered the student’s ability in writing for the tent grade students of SMA Negeri 2 Kuta Makmur? And (2) how do the students’ respond toward the implementation of PLEASE strategy in Learning writing for the tent grade students of SMA Negeri 2 Kuta Makmur? The purposes of this research are; 1) To empower the students’ ability in writing for the tent grade students of SMA Negeri 2 Kuta Makmur through implementation of PLEASE strategy 2) To know the students’ response toward the implementation of PLEASE strategy for the tent grade students of SMA Negeri 2 Kuta Makmur. The researcher used the collaborative classroom action research as the methodology of the research. Then the researcher did the collaboration with English teacher to do the research. The setting of this research was SMA Negeri 2 Kuta Makmur. The sample of this research was the tent grade Student of class x which total Students were 20 students. The instruments were used in this research such as: observation sheet and test for the researcher and students’, questionnaires, and field note. The data analysed through qualitative research. Based on the data finding, the researcher concluded that PLEASE strategy could improve students writing skill, this method could solve the students’ problem in writing the students had motivation and gave positive response towards the implementation of the method.